PENGARUH KUALITAS LABA, UKURAN PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN PADA SUBSEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2024 - Alica Karunia; Siti Nuraidawati (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to analyze the influence of earnings quality, firm size, and Corporate Governance on firm value in pharmaceutical subsector companies listed on the Indonesia Stock Exchange for the period 2020–2024. The research method used is a quantitative approach with panel data regression analysis, and the sample was obtained through purposive sampling based on the companies' annual financial reports. The results show that earnings quality has a significant effect on firm value, with a t-value of 2.078946 > t-table 2.013 and significance of 0.0446 < 0.05. Firm size does not have a significant effect on firm value, with a t-value of 1.284720 < t-table 2.013 and significance of 0.2069 > 0.05. Corporate Governance also does not have a significant effect on firm value, with a t-value of -1.399399 < t-table 2.013 and significance of 0.1700 > 0.05. Simultaneously, the three variables have a significant effect on firm value, as indicated by an F-value of 13.96289 > F-table 2.807 and significance of 0.000000 < 0.05. The coefficient of determination (Adjusted R-squared) is 76.04%, meaning the remaining 23.96% is influenced by other factors not examined in this study. Keywords: Earnings Quality; Firm Size; Corporate Governance; Firm Value